2013
DOI: 10.1007/s12035-013-8499-2
|View full text |Cite
|
Sign up to set email alerts
|

The Macamide N-3-Methoxybenzyl-Linoleamide Is a Time-Dependent Fatty Acid Amide Hydrolase (FAAH) Inhibitor

Abstract: The Peruvian plant Lepidium meyenii (Maca) has been shown to possess neuroprotective activity both in vitro and in vivo. Previous studies have also demonstrated the activity of the pentane extract and its macamides, the most representative lipophilic constituents of Maca, in the endocannabinoid system as fatty acid amide hydrolase (FAAH) inhibitors. One of the most active macamides, N-3-methoxybenzyl-linoleamide, was studied to determine its mechanism of interaction with FAAH and whether it has inhibitory acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
0
28
0
3
Order By: Relevance
“…Anandamide is involved in several physiological processes such as painful sensitivity and neuroprotection [16]. Selective FAAH inhibitors enhance anandamide endogenous levels that cause antinociceptive effect by agonism on the CB 2 receptor [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anandamide is involved in several physiological processes such as painful sensitivity and neuroprotection [16]. Selective FAAH inhibitors enhance anandamide endogenous levels that cause antinociceptive effect by agonism on the CB 2 receptor [21].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, limited evidence of efficacy against persistent pain has been described up to now [15]. However, in vitro studies confirmed macaenes family components' involvement in enhancing cannabinoid transmission [16]. The cholinergic stimulation induced by L. meyenii extract (mainly by polyphenols) has been related to memory improvement [17] as well as antioxidant properties that may sustain the antidepressant-like effects of the plant extract [18].…”
Section: Introductionmentioning
confidence: 99%
“…103 It has been shown that the macamide N-3-methoxybenzyl linoleamide weakly inhibits the major AEA degrading enzyme fatty acid amide hydrolase (FAAH, which is a membrane bound mammalian enzyme responsible for the destruction of a number of endogenous signaling amides by hydrolysis), and may thus exert indirect cannabimimetic neuroprotective effects. 75 This was recently confirmed in a study in which synthesized macamides and analogs were shown to act as FAAH inhibitors, although no further ECS targets were tested. 76 In some pharmacological experiments, the sexual behaviour of male rats and the erectile function of castrated rats were enhanced.…”
Section: Pharmacology Of Lepidium Meyeniimentioning
confidence: 95%
“…68 While the interactions of Echinacea NAAs with CB receptors have been studied in more detail, ECS-interacting NAAs from other plants have been described only recently. 72,73,75,76 The assumption that NAAs may interfere with the ECS due to their structural similarity to endocannabinoids such as anandamide (N-arachidonoylethanolamide, AEA) and palmitoylethanolamide 35 is intuitive, but the confirmation of this assumption is hampered by the lack of structure -activity relationship (SAR) data.…”
Section: Analgesic and Anticonvulsant Effectsmentioning
confidence: 99%
See 1 more Smart Citation